2007
DOI: 10.1246/bcsj.80.158
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of AC Impedance Measurements for Electrochemical Glucose Sensing Using Glucose Oxidase to Improve Detection Selectivity

Abstract: The electrochemical detection of glucose using glucose oxidase (GOx) has been conducted by means of AC impedance measurements. In the absence of glucose, the Nyquist plots were straight line due to a reversible redox reaction involving the electron mediator. On the other hand, the Nyquist plots became a circular arc in the presence of glucose, and its radius decreased with an increase in the glucose concentration. The shape of the Nyquist plots were explained with assistance of numerical calculations. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Electrical, ionic and mass transfer resistances can affectively be determined by using EIS . There are number of publications using electrochemical impedance spectroscopy method to study enzyme electrodes and microbial fuel cells . Jung and Hall applied EIS extensively to analyze catalytic response of GO x enzyme electrode in an organic salt .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical, ionic and mass transfer resistances can affectively be determined by using EIS . There are number of publications using electrochemical impedance spectroscopy method to study enzyme electrodes and microbial fuel cells . Jung and Hall applied EIS extensively to analyze catalytic response of GO x enzyme electrode in an organic salt .…”
Section: Introductionmentioning
confidence: 99%
“…and Kohma et al. reported an impedance simulation method and discussed the change in the shape of the electrochemical impedance spectra with the concentration gradient of the mediator on the electrode surface at each frequency . Samukawa et al.…”
Section: Introductionmentioning
confidence: 99%
“…The 3.6. Electrochemical impedance spectroscopy study of Ty based electrode (ITO/GNPs/NiO/poly(PPA)-Ty) EIS is a versatile technique describing the response of an electrochemical process taking place at the electrode solution interface [65]. It has been demonstrated that EIS measurements can provide significantly more sensitive responses than amperometric techniques for the detection of some biomolecules [66,67].…”
Section: Interfacial Properties Ofmentioning
confidence: 99%
“…In this case, if the cost of the membrane is expensive, the price of one biosensor tip may be very expensive. 8 Kuwabata et al [9][10][11] applied electrochemical impedance spectroscopy (EIS) to electrochemical glucose sensing without any selective permeable membranes. EIS is one of the nondestructive methods for measuring the current response to the application of sinusoidal AC voltage at various frequencies.…”
Section: Introductionmentioning
confidence: 99%